Preparing students for personality-oriented education in the pedagogical practices in the school-kindergarten Montessori - Січкар, Алла (Educological discourse, 2013)
The article is devoted the issue of the day of modern pre-school are preparations of educator, ready to the collaboration with a child from position of «creation, but not Creator», introduction of the personality oriented model of preschool education.